Inquiry-Based Approach in Biological Anthropology Education: Evidance of Early Bipedalism in Basal Hominins - Dimas Ario Sumilih (Universitas Sulawesi Barat, 2025)
This paper analyses the effectiveness of the guided inquiry approach in enhancing students’ understanding of evidence for early bipedalism in basal hominins, a topic that demands strong analytical skills for interpreting paleoanthropological data. The study adopts a qualitative approach, using a literature review to examine scientific publications, empirical reports, and theoretical discussions on implementing inquiry in biological anthropology education. The analysis focuses on patterns in the application of inquiry syntax, the use of fossil data representations, and their contribution to the development of students’ scientific process skills. The synthesis indicates that guided inquiry improves students’ understanding of early bipedal traits while strengthening their abilities in observation, question formulation, data classification, and drawing evidence-based conclusions. The literature also reports increased learning motivation and scientific attitudes when inquiry is implemented in a structured manner, even without direct laboratory-based fossil analysis. This paper concludes that guided inquiry is an effective pedagogical strategy for developing scientific literacy and enhancing students’ interpretative abilities regarding human evolutionary evidence.